The analysis of the key doctrines of Boko Haram (Jama’at Ahl-I- Sunnah Li Al-Da’wati Wa Al-Jihad). - Iyawa, Aisha Muhammad (AUC Knowledge Fountain, 2018)
The issue of Boko Haram has received considerable critical attention. It is one of the contemporary threats of the globe . They created a devastation that is having an adverse impact on Islam and the socioeconomic situation in the region and in some parts of Africa. There is a growing body of literature on Boko Haram, mostly focusing on the political aspects. Little emphasis has been put on the religious approach. This study is important because it will approach the issue from a religious perspective. This will be done by analyzing some of their doctrines to challenge and correct some of their misconceptions of Islam. Moreover, being a Nigerian from the North East and specifically from Borno state (Borno is the main center of Boko Haram), I have a special interest to study Boko Haram's religious perspective and views to correct misconceptions and spread awareness which may help in terminating the crisis of Boko Haram.